2023
DOI: 10.24425/bpasts.2023.144609
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spatial distribution and the type of material on the occurrence of bandgaps in phononic crystals

Sebastian Garus,
Wojciech Sochacki,
Paweł Kwiatoń
et al.

Abstract: The study investigated the effect of the fill factor, lattice constant, and the shape and type of meta-atom material on the reduction of mechanical wave transmission in quasi-two-dimensional phononic structures. A finite difference algorithm in the time domain was used for the analysis, and the obtained time series were converted into the frequency domain using the discrete Fourier transform. The use of materials with large differences in acoustic impedance allowed to determine the influence of the meta-atom m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Here, the materials were assumed to be linear elastic, homogeneous and isotropic, where properties were shown in table 1. It was noted that the below values represented typical material properties [38,39].…”
Section: The Geometric Structures and Theoretical Modeling 21 Geometr...mentioning
confidence: 99%
“…Here, the materials were assumed to be linear elastic, homogeneous and isotropic, where properties were shown in table 1. It was noted that the below values represented typical material properties [38,39].…”
Section: The Geometric Structures and Theoretical Modeling 21 Geometr...mentioning
confidence: 99%
“…These studies have shown the potential of active phononic crystals in controlling the propagation of waves at specific frequencies, offering the possibility of serving as directional mechanical filters. Another area of exploration has focused on understanding how factors such as the filling factor, lattice constant, and the shape and type of meta-atomic material affect the transmission of mechanical waves in quasi-two-dimensional phononic structures [12]. Such investigations provide crucial insights into designing structures with desired wave properties.…”
Section: Introductionmentioning
confidence: 99%